Green cotyledons of two Hakea species control seedling mass and morphology by supplying mineral nutrients rather than organic compounds - Lamont, Byron; Groom, Philip (2002)
•Hakea species dominate shrubby vegetation on seasonally dry, nutrient impoverished soils in Australia. We hypothesized that the exposed cotyledons control growth of the young seedling by providing it with mineral nutrients rather than C-based compounds. • Two representative species with differing seed masses were tested. Cotyledon removal caused large reductions in plant mass and dimensions, but little effect on specific leaf area. Cotyledons expanded markedly on germination although their chlorophyll content was much lower than the first leaves. Shading the cotyledons or applying a C-storage compound (inositol) to the soil had no consistent effect on seedling properties. • Cotyledon removal greatly reduced seedling P (especially), N, K, Ca, Mg and Cu, but not Fe or Mn, whereas shading the cotyledons had no effect. Transfer of mineral nutrients from the embryos to the seedlings in their natural soils varied from 90 to 2% (for P and Ca, respectively), and accounted for 79% of total content (P) to negligible (K, Ca, Fe) at 3 months. Cotyledons indirectly increased soil nutrient uptake. Addition of P, N or P + N after cotyledon removal had no benefit but addition of P + N + K + Mg + S restored morphology and nutrient content. • In nutrient and water-limited habitats with abundant light, cotyledons in Hakea spp. might serve to maximize supply of mineral nutrients to the shoots, which then maximize C-supply to the rapidly elongating roots.